Navigating Islam and Human Rights: Examining Women's Right to Refuse Pregnancy in Indonesia - Zuhriah, Erfaniah; Syahriana, Nur Alfy; Ali, Zezen Zainul (Journal of Southeast Asian Human Rights, 2024)
The purpose of this study is to examine whether women have the right to refuse pregnancy. This idea is an Islamic jurisprudence initiated by KH. Husein Muhammad, an Indonesian feminist scholar. This study analyzes the reasons for the emergence of Husein Muhammad's thoughts and provides constructive criticism. The article argues that in Indonesian society, married couples are always required to have children in their marriage. This demand leaves women with no opportunity to bargain over their position as bearers of the reproductive function, and even forces them to become pregnant. In contrast, Islam strongly upholds the interests and justice for women. By using a qualitative approach and literature, as well as data obtained by collecting references and documentation in accordance with the research theme, it was found that Husein Muhammad’s concept of women having the right to refuse pregnancy was influenced not only by the meaning of the text but also by the externalization of thoughts that arose as a result of the process of interaction and dialectics with the people around him. The objectivation process is carried out in the process of Husein Muhammad's self-interpretation of the knowledge that has been obtained, shaped by his history of studying women’s issues. Husein Muhammad based his thoughts on Islamic principles, namely justice, deliberation, equality, and peace. Therefore, the right to refuse pregnancy can be categorized as a natural right in human rights. However, the right is still bound to other aspects and is not fully applicable.   Keywords: Women’s Rights, Women’s Perspectives, Islamic Legal Construction, Discrimination, Husein Muhammad